Evaluation of Adulticidal Clorine with Black Sand, White Sand and Silica Sand for Decline Coliform Bacteria - Rezania Asyfiradayati; Eni Budiyati; Mitoriana Porusia; Muhammad Rivandi Athaya; Afnan Zain Muzakki; Jenita Berlian Nindyasari; Siti Rohana Mohd Yatim (Jurnal Kesehatan Lingkungan)
Introduction: The World Health Organization estimates that approximately 2.2 billion individuals globally lack access to safely managed drinking water supplies. The development of chlorine diffusers represents a promising intervention to address bacterial contamination, particularly coliform bacteria in water sources. To optimise their efficacy, rigorous analysis of chlorine diffusers’ performance and optimal material combinations is required to ensure a maximum reduction in coliform populations. Methods: The study population comprised all water sources in the Pabelan Kartasura Sukoharjo Village area, with a total sample volume of 720 litres. Subsequently, 100 mL aliquots were collected from each water reservoir using sterilised sampling bottles. Parameters assessed included temperature, pH, total dissolved solids (TDS), and coliform counts. Instrumentation for physicochemical analysis included thermometers, TDS meters, and digital pH meters, while coliform detection was conducted using the Compact Dry EC method. Each sample was evaluated at four time intervals: 0, 30, 45, and 60 minutes. Results and Discussion: Analysis revealed statistically significant differences in coliform bacterial counts among chlorine diffuser types incorporating silica sand, white sand, and black sand. Conversely, no statistically significant variations were observed for temperature, pH, or TDS across the experimental groups. These findings point out the importance of sand composition in enhancing chlorine diffusers’ antimicrobial efficacy. Conclusion: Chlorine diffusers incorporating diverse sand media demonstrated varying efficacy in reducing coliform bacteria, with black sand exhibiting the most pronounced reduction. This finding suggests that material selection significantly influences the functional performance of chlorine-based water disinfection systems.